2013
DOI: 10.1029/155gm22
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Forecasting of the Dst Index

Abstract: The Dst index can be predicted by an autoregressive moving average filter that transforms the solar wind electric field and dynamic pressure into changes in the index. Integration of these changes gives Dst. The maximum lead time possible is less than 60 minutes. Longer lead times are probably unobtainable due to the stochastic nature of IMF Bz. In this paper we use photospheric observations of the solar magnetic field to predict Dst. Our technique uses the Wang-Sheeley-Arge (W-S-A) model to forecast the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Note also that, since the strength of CIR-driven storms is usually weak to moderate [Tsurutani et al, 1995], many large flux events are associated with weaker storms with Dst > À100 nT. The results obtained in this paper for CIRassociated storms, however, can be naturally extended to the weaker CIR-related storms, considering the fact that our results are very similar as those of McPherron et al [2005]. Superposing all of the CIR events in 1995 about the stream interfaces, McPherron et al [2005] showed that the flux recovers to the prestorm level 1 day after the interface arrival, and enhances about one order of magnitude larger than the prestorm level in a few days.…”
Section: S09004supporting
confidence: 72%
See 1 more Smart Citation
“…Note also that, since the strength of CIR-driven storms is usually weak to moderate [Tsurutani et al, 1995], many large flux events are associated with weaker storms with Dst > À100 nT. The results obtained in this paper for CIRassociated storms, however, can be naturally extended to the weaker CIR-related storms, considering the fact that our results are very similar as those of McPherron et al [2005]. Superposing all of the CIR events in 1995 about the stream interfaces, McPherron et al [2005] showed that the flux recovers to the prestorm level 1 day after the interface arrival, and enhances about one order of magnitude larger than the prestorm level in a few days.…”
Section: S09004supporting
confidence: 72%
“…A slow stream occasionally associated with a heliospheric current sheet [Smith, 2001] is compressed ahead of the stream interface, while a highspeed stream with large-amplitude Alfvé nic fluctuations originating from a solar coronal hole follows the stream interface [Tsurutani et al, 2006]. A gradual density increase with the westward flow deflection exists about a half day before the arrival of the stream interface [McPherron et al, 2005]. It is worthwhile noting here that, as shown in this picture, a CME-related disturbance is nearly a radial profile of the solar wind structure, while a CIR-related disturbance is nearly an azimuthal profile.…”
Section: Event Selectionmentioning
confidence: 99%
“…Note that the probabilistic forecast of Kataoka and Miyoshi (2006) is a similar concept of daily and weekly probability of the meteorological precipitation forecast. McPherron and Siscoe (2004) and McPherron et al (2005) proposed similar probability forecast for the prediction of the Dst index.…”
Section: Introductionmentioning
confidence: 99%
“…Although much research has been done on prediction of the D s t index, much less has been done on probabilistic forecasting of D s t . One such work described in McPherron et al [] involves identification of high speed solar wind streams using the WSA model [see Wang and Sheeley , ], using predictions of high speed streams to construct ensembles of D s t trajectories which yield the quartiles of D s t time series.…”
Section: Introductionmentioning
confidence: 99%